Clinicopathological features and outcomes of coexistent light chain cast nephropathy and light chain deposition disease in patients with newly diagnosed multiple myeloma. Issue 10 (29th June 2021) - Lin, Zi-Shan; Zhang, Xu; Li, Dan-Yang; Yu, Xiao-Juan; Qin, Ai-Bo; Dong, Yujun; Zhou, Fu-De; Wang, Suxia; Zhao, Ming-Hui
Abstract : Aims: A varying proportion of patients with multiple myeloma suffer from more than one type of kidney disease simultaneously, of which the most common pattern is coexistent light chain cast nephropathy and light chain deposition disease (LCCN+LCDD). We investigated clinicopathological characteristics and outcomes of LCCN+LCDD in comparison with pure LCCN and pure LCDD. Methods: We retrospectively analysed 45 newly diagnosed multiple myeloma patients with pure LCCN (n=26), LCCN +LCDD (n=9) and pure LCDD (n=10) between 2000 and 2019 at Peking University First Hospital. Results: Pathologically, patients with LCCN+LCDD were more likely to have λ light chain isotype and presented atypical features of LCDD including less nodular glomerulosclerosis and less deposit distribution than patients with pure LCDD. In clinical characteristics, patients with LCCN +LCDD and patients with pure LCCN shared similar features. The death-censored renal survival in patients with LCCN +LCDD was similar to patients with pure LCCN but worse than patients with pure LCDD, but the overall survival was much better than patients with LCCN alone and similar to patients with pure LCDD. For patients with pure LCCN, the independent predictor of death-censored renal survival was lactate dehydrogenase, and the independent predictors of overall survival were the mean number of casts and serum albumin. Conclusions: Patients with LCCN+LCDD had similar renal outcome compared with patients with pure LCCN but the overall survival is much better. Thus, for patients with LCCN, especially those with λ restriction, pathologists should carefully evaluate the kidney specimens to exclude the possibility of combined LCDD.